Comparison of Durability and Gamma-Ray Shielding Performance of High-Velocity Oxygen Fuel Tungsten Carbide-Based Coatings on Cold-Rolled Steel Surface - Yeong-Ho Son; Seung Heon Baek; Beom Kyu Kim; Jeong Ho Hwang; Jae Hun Lee; Geun Dong Song (Crystals)
This paper provides a comparative evaluation of the mechanical properties, corrosion resistance, and gamma-ray shielding performance of four different types of tungsten carbide (WC)-NiCr coatings deposited on cold-rolled steel surfaces, which are used as materials for low- and intermediate-level radioactive waste (LILW) storage containers. The four types of coatings were classified as WC-85, WC-73, WC-66, and WC-39 according to their WC content and were applied to the cold-rolled steel surfaces using the High-Velocity Oxygen Fuel (HVOF) spraying process. The performance of the layered coatings was analyzed in terms of their microstructure, hardness, wear resistance, adhesion strength, corrosion properties, and gamma-ray shielding characteristics. Coatings with elevated WC contents showed enhanced mechanical properties and gamma-ray shielding effectiveness, whereas coatings with relatively lower WC contents and higher NiCr contents exhibited greater corrosion resistance. This paper discusses the performance of WC-NiCr coatings from the viewpoint of enhancing the durability and safety of commercial LILW storage containers.